Why do taxpayers comply: Evidence from Indonesia - Yussof, Salwa Hana; Isa, Khadijah; Adriani, Desri Eka; Mohdali, Raihana (Penerbit UMT, Universiti Malaysia Terengganu, 2016)
This paper aims to identify the reasons used by taxpayers to become a compliant taxpayer, and whether these reasons are affected by demographic factors. Five reasons were used - fairness on the distribution of tax burden, fairness of the government in utilising government revenue, peer influence, sanctions and non-tax macro factors. Data was collected using questionnaire survey distributed to government officers in Pelalawan Regency, Riau Province, Indonesia. The results showed that fairness, peer influence and sanctions are among the reasons used by taxpayers when they decide to comply with income tax laws. The choice of these reasons are not affected by age, gender and level of study, except on fairness of the government in utilising government revenue.